Functional analysis methods for reliability models - Gupur, Geni.; SpringerLink (Online service). (Basel, Switzerland Birkhäuser Basel, 2011)
The main goal of this book is to introduce readers to functional analysis methods, in particular, time dependent analysis, for reliability models. Understanding the concept of reliability is of key importance ? schedule delays, inconvenience, customer dissatisfaction, and loss of prestige and even weakening of national security are common examples of results that are caused by unreliability of systems and individuals. The book begins with an introduction to C0-semigroup theory. Then, after a brief history of reliability theory, methods that study the well-posedness, the asymptotic behaviors of solutions and reliability indices for varied reliability models are presented. Finally, further research problems are explored. Functional Analysis Methods for Reliability Models is an excellent reference for graduate students and researchers in operations research, applied mathematics and systems engineering
Preface -- C0-Semigroup of Linear Operators and Cauchy Problems -- Statement of the Problems -- The System Consisting of a Reliable Machine, an Unreliable Machine and a Storage Buffer with Finite Capacity -- Transfer Line Consisting of a Reliable Machine, an Unreliable Machine and a Storage Buffer with Infinite Capacity -- Further Research Problems -- Bibliography.
Electronic reproduction.
Keywords: Reliability (Engineering) -- Mathematics; Functional analysis